Cognitive dimensions of subjective quality of life in Hajdú-Bihar county - Sőrés, Anett (Applied Studies in Agribusiness and Commerce, 2013)
The objective of the present study is an investigation of the objective and subjective factors of life quality. Researchers and political leaders show increasing interest in the question: on what grounds do people judge their quality of life, what satisfies or makes them happy? Do we subconsciously make some kinds of mathematical calculations weighing our results achieved in certain areas of life to assess how we are getting on? Or rather we use one “indicator” (e.g. money, number of friends, professional recognition) and we assess our situation accordingly? These issues necessarily emerge when it comes to the consideration of the quality of life. Among factors determining life satisfaction, earnings, employment, health and relationships play significant roles. Therefore, on the leading edge of this research are primarily the cognitive factors of life quality, i.e. external factors influencing satisfaction. The present study also seeks to identify the role of health tourism in the assessment of the quality of life. Questionnaires were completed in one of the most popular tourist destinations of Hajdú-Bihar County. The 805 local respondents expressed their views primarily about factors determining their well-being and about the impacts of the dominant presence of health tourism on their lives.